Analysis of the Business Environment and Entrepreneurship Strategy in Improving SME Culinary Enterprises - Mutmainna, Mutmainna; Kumalasari, Tien; Yunarti, Yunarti (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
Culinary is a service provider for everyone's basic needs and along with the times, culinary has also become a business trend in society. The purpose of this research is to find out (1) analysis of the business environment and entrepreneurial strategies in improving SME culinary businesses, (2) the best alternative strategies in improving SME culinary businesses. The research method used is descriptive qualitative. The data analysis used is descriptive qualitative in describing the business environment in UKM Salenrang. The results of the analysis of the internal business environment in UKM Salenrang are: (a) HR aspects, (b) financial/accounting aspects, (c) production/operations aspects, and (d) marketing aspects, while the analysis of the external business environment is: (a) strengths economic, (b) technological power, (c) social power, and (d) political power. The results of the entrepreneurial strategy analysis using SWOT analysis by identifying the internal factors of Salenrang SMEs, namely strengths: quality raw materials, affordable product prices, comfortable and strategic shopping places, varied product types and tastes, service, complete public facilities, application discounts, and a neat and clean room design. Meanwhile, weaknesses include a business management system that is not yet optimal, marketing promotions that are not yet intensive and packaging for some products that is less attractive. Identify external factors, namely opportunities, including government policies that support the development of SMEs in Maros Regency, while the threats faced are competitors that have emerged. This condition puts Salenrang SMEs in a growth position.